County Health Leadership Practices and Readiness for Noncommunicable Disease Services in Kenya - Paul Wekesa; Kevin Owuor; Cheryl Beers Cullen (Ubiquity Press, 2022)
Background: Premature mortality from noncommunicable diseases (NCDs) is a contemporary development challenge. Low-income and lower-middle-income countries are disproportionately affected, with the poorest in society considered the most vulnerable. A paucity of literature exists on how leadership practices at the implementation level relate to ensuring readiness for NCD services. Objective: This study investigated any relationship between leadership practices and readiness for NCD services. Methods: This correlational study investigated any relationship between leadership practices at the county level and readiness for NCD services in Kenya using secondary data from a 2013 Service Availability and Readiness Assessment survey. Correlation and multiple linear regression tests were used to determine the strength and direction of any relationship between leadership practices (annual work planning, therapeutic committees, and supportive supervision), and NCD readiness (county readiness score). Findings: The findings indicated a statistically significant relationship between therapeutic committee ('p' = .002) and supportive supervision practices ('p' = .023) and NCD readiness. Leadership practices also had a statistically significant predictive relationship with NCD readiness ('p' = .009). Conclusion: Health leaders should ensure that leadership practices that have a predictive relationship with NCD readiness, such as therapeutic committee activities and supportive supervision visits, are implemented appropriately. Further, county health leaders should pay particular attention to the implementation of these leadership practices at nonpublic and Tiers 2, 3, and 4 health facilities that had lower NCD readiness scores.